Concepção e análise de estratégias de gerenciamento de potência aplicadas ao controle de nanorredes C.C. com barramentos interconectados - Silva, Edivan Laercio Carvalho da (2021)
This thesis proposes the conception and analysis of power management strategies applied to the control of multiple buses dc nanogrids. Nanogrids are small-scale commercial and residential prosumer electrical installations that, typically, involves photovoltaic generation systems, energy storage, and critical loads at extra-low voltage levels. In this work, a new power management strategy is proposed, based on a price response theory and droop control loops. The pricing strategy is used as a simple methodology to define operation modes for each power element. This allows improving the efficiency of the power management, because is not necessary a power-sharing mode all the time. The power management is implemented in a distributed way to control interconnected systems. To validate this proposal, the price-based power management was applied in a dc nanogrid that includes a low voltage dc bus, at 380 V, interconnected through an interlink converter to one or more extra-low voltage buses, at 48 V. These voltage levels are in accordance with industry standards and regulations for dc power distribution, whose standardization is under development with the IEC. The 380 V bus is used to connect the system to ac grid, photovoltaic systems, and other high-power loads. In this system, the 48 V bus is used to supply light loads, but which commonly have higher priority due to the nature of their application, such as electronic devices, data centers, emergency lights and others. The main contribution of the work was the conception of a simple tool that makes it easier for the end-user to carry out the power management of the nanogrid, such as load prioritization, energy storage, and tariff variations of the distribution system. Simulation and experimental results are presented to validate the proposed concepts.